PENGARUH PENAMBAHAN SEKAM PADA PEMBUATAN KOMPOS DARI BAHAN ORGANIK - Riska, Rina Afrinata; Febriyanti, Iko Sabrina; Ayunda, Nur (Universitas Mataram, 2024)
Composting is one of the best ways to manage organic waste. The purpose of this study was to study how the addition of rice husks to the process and quality of compost made from dry leaves. Rice husks were chosen as an additive because they are easy to find and have the ability to absorb moisture. In this study, various proportions of rice husks were added to the mixture of dry leaf materials. During the composting process, temperature, humidity, pH, and carbon and nitrogen levels were observed. The results showed that the addition of rice husks significantly affected the process rate and quality of the compost, with certain proportions of rice husks producing compost with an ideal ratio. The addition of rice husks was also shown to accelerate the composting time and increase the stability and structure of the compost. Therefore, the use of rice husks as an additive in composting can be suggested as an effective and sustainable solution in managing organic waste.